Community-Based Training as a Solution to Fluctuating Poverty in Sub-districts (LPPM Universitas PGRI Adi Buana Surabaya, 2025)
Poverty in urban areas such as the subdistricts (kelurahan) of Buleleng Regency shows significant fluctuations, even though the overall poverty rate has declined. This phenomenon indicates unstable welfare dynamics, particularly among vulnerable groups within the lowest three income deciles. This policy study aims to identify the main causes of poverty fluctuation and formulate relevant policy alternatives for local government implementation. Based on secondary data analysis from BPS and the Coordinating Ministry for Human Development and Culture (Kemenko PMK), along with theoretical reviews, the core issue lies in the instability of household income caused by low human resource competitiveness and the limited provision of government-supported skills training programs. The Human Capital Theory framework is applied to emphasize the importance of investing in human capacity development as a sustainable poverty alleviation strategy, compared to the Infrastructure-Led Development approach, which requires higher costs and extensive land resources. The study proposes three policy alternatives: (1) vocational and entrepreneurship training, (2) participatory community-based training, and (3) training integrated with basic service infrastructure. Using Bardach’s analytical framework—covering technical, economic, political, and administrative feasibility—the participatory community-based training approach emerged as the most viable option. This policy highlights community involvement in designing and implementing training programs aligned with local needs, continuous mentoring, and collaboration with local stakeholders. Its implementation is expected to enhance human resource competitiveness, strengthen community economic independence, and reduce poverty fluctuation sustainably. The study recommends allocating at least 50% of subdistrict funds to community-based training initiatives, supported by measurable indicators of success such as post-training productivity, self-reliance, and community welfare improvement.